Transición del SG-SST basado en la norma NTC OHSAS 18001:2007 al SG-SST basado en la norma NTC ISO 45001:2018, con enfoque hacia el fortalecimiento de la cultura de prevención para la empresa Aviatek S.A.S. (2021)
The following article develops a proposal for the transition of the SG-SST under ISO 45001:2018, through a current diagnosis in the company Aviatek S.A.S. and the design of a structure that allows to achieve compliance with the duties of the ISO 45001:2018 standard, Aviatek S.A.S. is a company that provides services in the hydrocarbon sector, being one of the most demanding sectors in the SG-SST, that is why it is presented as an opportunity for improvement the strengthening of the transition of the management system with the introduction of a preventive culture based on the application of a validated questionnaire and the proposal of tools as a solution to the initial diagnosis of the company Aviatek S.A.S., Additionally, the development of a self- assessment of compliance with the requirements of the ISO 45001 standard, the structure of the system by stages and finally the execution of items four to eight, context of the organization, leadership and participation of workers, planning, support and operation are presented.